Economic development : theory, policy, and international relations - Little, I. M. D. (New York : Basic Books, 1982)
This book is on the survey of development economics, including the main international economics issue that have giving rise to north-south confrontation.
"A Twentieth Century Fund book."
Includes indexes.
Bibliography: p. 425-439.
oo 25/10/18
Loans
Keywords: Economic development; International economic relations; Developing countries